LANGUAGE CHOICE AND DIALECT USE AMONG ENGLISH DEPARTMENT STUDENTS IN INFORMAL CAMPUS INTERACTION - Fazria A. Hulamahe; Indrawati Adam; Aulia Mundok; Muziatun Muziatun (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study examines language choice and dialect use among English Department students in informal campus interaction at Universitas Negeri Gorontalo. Using a descriptive quantitative survey design, data were collected from 17 students through a Google Forms questionnaire consisting of closed and open-ended questions. The findings show that students use different language varieties depending on context, interlocutor, and communicative purpose. Mixed language is dominant in classroom discussion and social media interaction, while Indonesian is frequently used when communicating with friends and lecturers. Local languages are mostly used at home and among peers who share similar regional backgrounds. The study indicates that students’ language choices are shaped by formality, solidarity, ease of communication, and identity negotiation.